2020
DOI: 10.4081/itjm.2020.1406
|View full text |Cite
|
Sign up to set email alerts
|

Management of COVID-19 in comorbidities

Abstract: As the main title ‘COVID-19 revolution: a new challenge for the internist’ states, the global coronavirus infection disease 2019 (COVID-19) pandemic represented a new challenge for the internists. This paper is part of a series of articles written during the difficult period of the ongoing global pandemic and published all together in this fourth issue of the Italian Journal of Medicine, with the aim of sharing the direct experiences of those who were the first to face this severe emergency, expressing each po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Our random forest model showed the importance of the long-term exposure to PM 10 on the COVID-19 severity and mortality prognosis versus other clinical variables clearly stated as comorbidities, such as COPD/asthma , cancer , diabetes and obesity, among others ( Cardamone and Donatiello, 2020 , Kong et al, 2021 , McGurnaghan et al, 2020 , Mohammad et al, 2021 , Oh and Song, 2021 ). Notwithstanding, we also found that age, sex (male) and obesity significantly increased the severity of COVID-19, which is in agreement with other studies ( Elezkurtaj et al, 2021 ).…”
Section: Discussionmentioning
confidence: 76%
“…Our random forest model showed the importance of the long-term exposure to PM 10 on the COVID-19 severity and mortality prognosis versus other clinical variables clearly stated as comorbidities, such as COPD/asthma , cancer , diabetes and obesity, among others ( Cardamone and Donatiello, 2020 , Kong et al, 2021 , McGurnaghan et al, 2020 , Mohammad et al, 2021 , Oh and Song, 2021 ). Notwithstanding, we also found that age, sex (male) and obesity significantly increased the severity of COVID-19, which is in agreement with other studies ( Elezkurtaj et al, 2021 ).…”
Section: Discussionmentioning
confidence: 76%
“…Since December 2019, the Coronavirus Disease-19 (COVID-19) pandemic has become the most challenging issue throughout the world. Many studies have been done on the nature of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) and its therapeutic strategies (Cardamone and Donatiello 2020;Schlosser et al, 2020).…”
Section: Introductionmentioning
confidence: 99%